The Relationship Maternal Support and The Habit Of Prone In Children Aged 0-3 Months - Trisha Kania Sugandi; Iis Aisyah; Heri Ridwan (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Children aged 0-3 months represents a critical period for child development, especially in the acquisition of gross motor skills. One recommended form of early stimulation during this stage is the prone position or tummy time, which plays an essential role in strengthening the neck, back, and shoulder muscles and supporting the achievement of subsequent developmental milestones. The successful implementation of tummy time is strongly influenced by maternal support as the primary caregiver, encompassing emotional, instrumental, informational, and appraisal support. This study aimed to examine the relationship between maternal support and tummy time habits among infants aged 0-3 months in Mekarjaya Village, North Sumedang District. A quantitative approach with a correlational design was employed. The study sample consisted of 72 mothers with infants aged 0-3 months, selected using a total sampling technique. Data were collected using validated and reliable questionnaires measuring maternal support and tummy time habits. Statistical analysis was conducted using Pearson’s correlation test. The findings revealed that most mothers demonstrated a very high level of support, while infants’ tummy time habits were predominantly categorized as good and very good. Bivariate analysis indicated a significant and very strong positive relationship between maternal support and tummy time habits (p < 0.001; r = 0.797), suggesting that higher levels of maternal support are associated with more optimal tummy time practices. These results highlight the crucial role of maternal involvement in promoting early motor stimulation. Therefore, it is recommended that healthcare professionals enhance educational and guidance programs for mothers regarding the importance of regular and appropriate tummy time practices to support optimal motor development in early infancy.